The millennials: Adversity intelligence and work engagement - Sowanya Ardi Prahara; Ros Patriani Dewi; Kamsih Astuti (Universitas Pendidikan Ganesha, 2020)
The industrial world is transforming towards the era of revolution 4.0 and society 5.0. In this era, digital technology is applied and becomes the center of human life. Demand that the millennial generation who currently dominates the job market in Indonesia have adversity intelligence so that they can be more engaged in their work and have a positive impact on company performance and development. This study aims to determine the relationship between adversity intelligence and work engagement in the millennial generation. Subjects in this study were 214 employees, aged 20-39 years who live in Yogyakarta and have worked at least one year. The data collection method in this study uses a Likert scale model. Data were collected using the Work Engagement Scale and the Adversity Intelligence Scale, by sending the scale via Google Form to respondents. The data analysis technique used is the product-moment correlation from Karl Pearson. Based on the data analysis, the correlation coefficient (R) was obtained for 0.820 (p <0.01). These results indicate that there is a very significant positive relationship between adversity intelligence and work engagement among millennial employees living in Yogyakarta. This study provides an overview of the level of work engagement and adversity intelligence for millennial generation employees, so as to increase the work engagement of millennial generation employees by increasing their adversity intelligence.